Smooth Particle Hydrodynamics-Based Characteristics of a Shaped Jet from Different Materials - Yin, J.P.; Shi, Z.X.; Chen, J.; Chang, B.H.; Yi, J.Y. (Проблемы прочности, 2019)
The liner material is one of the key factors in the design of armor-piercing ammunition that effect the penetration efficiency. The performance of a shaped jet formed by the charge liner is determined by different properties of the material under the blasting action, in particular for the target with explosive reactive armor, which diminishes the penetration power by dispersing the shaped jet. The performance of shaped jet elements from different materials is studied, AUTODYN finite element software and smooth particle hydrodynamics method are employed to simulate the formation of shaped jet elements from the three materials: Cu, PTFE, and PTFE/Cu and their penetration into target plates, which was verified in the experiment. A shaped jet for a Cu liner is shown to be formed under the action of a detonation wave, while PTFE and PTFE/Cu materials generate a dispersive particle jet. The head velocity of a Cu jet is found to be the lowest, the penetration depth is the deepest, and the penetration hole size is the smallest; the velocity of a PTFE particle jet is the highest and the penetration depth is the shallowest, the penetration hole size takes the mid-position; the head velocity and penetration depth of a PTFE/Cu jet take the mid-position, while the penetration hole is the largest. The PTFE/Cu jet possesses higher penetration performance as compared to the PTFE jet, and its hole-opening capability is improved as compared to the Cu jet.